Depression and distress in couples with infertility - who suffers more? - Pejušković Bojana; Tošković Oliver; Ivanišević Milica; Lero Marija; Durutović Otaš (Srpski Arhiv za Celokupno Lekarstvo, 2023)
Introduction/Objective. Infertility is the inability to achieve pregnancy after a year or more of unprotected sexual intercourse. It is a clinical and social issue affecting both sexes. Infertility can cause anxiety, depression, and personal distress with long-lasting consequences. Men and women tend to cope with infertility in different ways and reliance on certain coping mechanisms can be harmful. This study aims to examine the correlative effects of infertility, distress and depression among couples, and investigate sex disparities in levels of suffering. Methods. The research is a cross-sectional study that included 168 participants (84 couples) divided into two groups, control and infertility group. Beck Depression Inventory Second Edition (BDI-II) and the Brief Symptom Inventory (BSI) were used to identify and assess psychological symptoms. Statistical analysis was performed using SPSS at the 0.05 level of significance. Results. The results showed that there was a significant difference in the scores on BDI and BSI scales between the infertile and fertile groups, with participants in the infertile group reporting higher levels of depression and distress (t = -2.724, df = 166, p < 0.01; t = -3.609, df = 166, p < 0.01). Women had significantly higher scores on the depression scale than men (t = -2.079, df = 166, p < 0.05). Conclusion. In summary, the study found that couples dealing with infertility experience higher levels of distress and depression compared to the control group. Women in these couples are particularly vulnerable to depression. The study highlights the importance of addressing the mental health needs of individuals and couples dealing with infertility, in addition to treating the underlying medical issues.